2020
DOI: 10.1002/pol.20200409
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline‐developable and negative‐type photosensitive polyimide with high sensitivity and excellent mechanical properties using photo‐base generator

Abstract: An alkaline developable and negative‐type PSPI with a high sensitivity and excellent mechanical properties based on a poly(amic acid) (PAA) and a photo‐base generator has been developed. The PAA was prepared by the polycondensation of p‐phenylenediamine (PDA) with an equimolar of 3,3′,4,4′‐biphenyltetracarboxylic dianhydride (BPDA) and 4,4′‐(hexafluoroisopropylidene)diphthalic anhydride (6‐FDA) and converted thermally to the corresponding polyimide, PI(PDA‐BPDA/6‐FDA). PI(PDA‐BPDA/6‐FDA) showed the high therma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Goto et al prepared a series of PIs with low D k s by introducing bulky diphenyl fluorenylidene moieties and concluded that the D k values of PIs were closely related to the imide group content (Imide%) in the repeating unit and fluorine content (F%). Based on their findings, various PIs with low D k have been reported. Our previous works on low D k PIs also revealed that incorporation of phenylene ether and adamantyl and alicyclic units to dianhydrides and diamines could effectively decrease the D k values of PIs. Most of the above studies focused on the development of PIs with low D k values at lower frequencies (1 kHz to 10 MHz). , However, few studies investigate the molecular structure of PIs with low D k as well as low D f . In particular, there is no clear guideline for designing PIs with both low D k and low D f , which is very important for the emerging 5G mobile communications technology. Therefore, it is of great interest and a challenge to establish the design concept of low D k and low D f PIs.…”
Section: Introductionmentioning
confidence: 99%
“…Goto et al prepared a series of PIs with low D k s by introducing bulky diphenyl fluorenylidene moieties and concluded that the D k values of PIs were closely related to the imide group content (Imide%) in the repeating unit and fluorine content (F%). Based on their findings, various PIs with low D k have been reported. Our previous works on low D k PIs also revealed that incorporation of phenylene ether and adamantyl and alicyclic units to dianhydrides and diamines could effectively decrease the D k values of PIs. Most of the above studies focused on the development of PIs with low D k values at lower frequencies (1 kHz to 10 MHz). , However, few studies investigate the molecular structure of PIs with low D k as well as low D f . In particular, there is no clear guideline for designing PIs with both low D k and low D f , which is very important for the emerging 5G mobile communications technology. Therefore, it is of great interest and a challenge to establish the design concept of low D k and low D f PIs.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the resulting PI thin film also exhibited high thermal stability, specifically with excellent ductility, high dimensional stability and even low dielectric properties. 100 Nowadays, negative-type PSPIs based on PAA have been widely developed with PBGs. 101 For instance, Chang et al found that the high optical transparency and low rigidity of the polyimide backbone give a significant promotion on the performance of PSPI, especially for the photosensitivity, owing to the designed wide optical bandgap and low rigidity are beneficial for the photochemical reaction and chemical imidization.…”
Section: Photobase Generators: Towards High-quality Photoresistsmentioning
confidence: 99%
“…The dissolution rate of PAA in TMAH solution is overly high to obtain a sufficient dissolution contrast between unexposed and exposed areas; thus, photosensitizers are added to the polymer matrix. According to the reaction mechanism, photosensitizers can be divided into two categories: photoacid generators (PAGs) 86 , 89 , 90 and photobase generators (PBGs) 85 , 88 , 91 .…”
Section: Micropatterning Of Polyimidementioning
confidence: 99%
“…Notably, PSPI involves photopatternable PI with photoactive agents and photopatternable PI precursors, such as poly(amic acid) (PAA) or poly(amic ester) (PAE) with photosensitive compounds 85 . The PSPI films are selectively exposed to UV light with a mask, allowing the exposed area to undergo a chemical change, such as cross-linking (negative tone) [86][87][88][89][90][91] and chain scission (positive tone) [92][93][94][95][96][97][98] ; undesired areas are dissolved in the developing solution. Methods for incorporating a wide variety of photochemistries into PI systems has been previously reviewed 84,85,99 .…”
Section: Photo Patterningmentioning
confidence: 99%